An Analysis of EFL Student's Needs of a Critical Literacy Model - Rizqiani, Diyah Ayu; Elida, Yusti (SCOPE: Journal of English Language Teaching, 2025)
This study aims to analyze the needs of English as a Foreign Language (EFL) students regarding a critical literacy model. The research sought to identify gaps in current EFL curricula and determine how a critical literacy approach could enhance students' language skills and critical thinking abilities. This study employs qualitative approach. There are two kinds of instruments used to collect data. First, a needs assessment questionnaire administered to 82 undergraduate EFL students in two private universities in Yogyakarta. They were the third semester students who enrolled Critical Reading class in English Language Education Study Program. Second, semi-structured interviews conducted with 3 lecturers who handled Critical Reading classes. The study participants were selected through purposive sampling to ensure representation across different proficiency levels and academic backgrounds. The findings revealed that 78% of students expressed a strong desire for more opportunities to engage with authentic texts critically. Furthermore, 85% of instructors acknowledged the importance of integrating critical literacy skills into their teaching but cited a lack of resources and training as primary obstacles. Based on these findings, the current study would become the basis to develop a critical literacy model tailored to EFL contexts, emphasizing the need for targeted professional development for instructors and the creation of culturally relevant teaching materials.